Perception of STML students toward the consumption of nuclear energy in electricity generation - Cheu, Fook Yoong; Mohd Shafie, Shafini (Universiti Utara Malaysia, 2020)
Nuclear energy is valid and plentiful. Nuclear energy produces high amounts of electricity without damaging the environment and atmosphere compared to the burning of fossil fuels (oil, gas, coal). The aim of this study was to identify the STML students' view about the knowledge, trust, perceived benefit, perceived risk toward the consumption of nuclear energy and study the relationship between knowledge, trust, perceived benefit and perceived risk with the consumption of nuclear energy in electricity generation. The quantitative method was used to conduct this study by a distributed questionnaire. There were high awareness and knowledge that had exposed to the STML students and due to the concern among the respondents about the safeties of nuclear energy to the country and the public, respondents scared to accept nuclear energy in Malaysia although nuclear energy has a large benefit to them. In the future, this study can focus on a different level of the age of people in an area by comparing opinions with this study.